2013
DOI: 10.1007/s00580-013-1854-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ketamine on oxidative stress following lipopolysaccharide administration

Abstract: This study investigated the effect of the serotonin selective reuptake inhibitors (SSRIs) fluoxetine, sertraline, fluvoxamine and the tricyclic antidepressant (TCA) impiramine on oxidative stress in brain and liver induced by lipopolysaccharide administration in mice. Each drug was administered subcutaneously at doses of 10 or 20 mg/kg, for two days prior to intraperitoneal (i.p.) administration of lipopolysaccharide E (LPS: 200 µg/kg). Mice were euthanized 4 h after administration of the lipopolysaccharide. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 109 publications
(66 reference statements)
5
17
1
Order By: Relevance
“…In fact, we found that all Fluvoxamine-treated rats did not show a preference for the use of the left forelimb (unimpaired) in the cylinder test suggesting a reduced toxic effect of the neurotoxin 6-OHDA due to the treatment. This major finding agreed with results from previous studies that showed that antidepressants can reduce MDA levels thereby significantly protecting striatal, prefrontal, and hippocampal cells and preventing neuronal loss associated with both chronic stress and 6-OHDA neurotoxicity [83][84][85][86][87]. We, therefore, postulated that Fluvoxamine possesses antioxidant properties (responsible for mopping up the free radicals generated by the autooxidation of 6-OHDA) and antitoxicity potential that reduced 6-OHDA neurotoxicity.…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 90%
“…In fact, we found that all Fluvoxamine-treated rats did not show a preference for the use of the left forelimb (unimpaired) in the cylinder test suggesting a reduced toxic effect of the neurotoxin 6-OHDA due to the treatment. This major finding agreed with results from previous studies that showed that antidepressants can reduce MDA levels thereby significantly protecting striatal, prefrontal, and hippocampal cells and preventing neuronal loss associated with both chronic stress and 6-OHDA neurotoxicity [83][84][85][86][87]. We, therefore, postulated that Fluvoxamine possesses antioxidant properties (responsible for mopping up the free radicals generated by the autooxidation of 6-OHDA) and antitoxicity potential that reduced 6-OHDA neurotoxicity.…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 90%
“…An important finding of our study consists in the lack of significant differences in cortical amounts of antioxidant enzymes between early ketamine-treated mice and controls. This result might appear contrasting with preclinical evidence describing, instead, a decreased activity of SOD and CAT in the PFC of ketamine-treated rats ( de Oliveira et al, 2009 ), as well as a reduction of GSH concentration ( Abdel-Salam et al, 2015 ). However, in these previously published studies, ketamine exposure occurred in adult life.…”
Section: Discussioncontrasting
confidence: 79%
“…In the present study, the ET levels in the liver homogenate and serum of BCS rats was positively correlated with MDA levels and negatively correlated with SOD levels, suggesting that ET may damage the liver through OS, which is supported by the results of studies on other types of liver injury ( 16 ). This is due to ligation of the IVC posterior to the liver resulting in an obstruction of outflow from the hepatic veins and IVC, leading to hepatic congestion and hypoxia, resulting in the production of a large number of ROS, which may activate hypoxia-inducible factor (HIF)-1, nuclear factor (NF)-κB, and various cytokines, consequently activating HSC to cause hepatic fibrosis ( 22 ).…”
Section: Discussionsupporting
confidence: 86%
“…When hepatic congestion occurs, intestinal ET enters the portal vein ectopically ( 14 , 15 ). Early studies have reported that ET participates in liver congestion injury ( 16 , 17 ). According to the present hypothesis, OS also has an important role in BCS, but studies to evidence this are currently lacking.…”
Section: Introductionmentioning
confidence: 99%